Evidence on the effects of inflation on price dispersion under indexation - Sven Schreiber; Juliane Scharff (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
Distortionary effects of inflation on relative prices are the main argument for inflation stabilization in macro models with sticky prices. Under indexation of nonoptimized prices those models imply a nonlinear and dynamic impact of inflation on the cross-sectional price dispersion (relative-price variability, RPV). Using US sectoral prices we estimate (a generalized form of) the theoretical relationship between inflation and RPV. We confirm the impact of inflation fluctuations but find hitherto neglected endogeneity biases, and our IV and GMM estimates indicate that average (trend) inflation is significant for indexation. Lagged inflation is less important.
urn:nbn:de:101:1-2008110434
Keywords: E31; C22; 330; relative price variability; trend inflation; endogeneity bias